Association between various insulin resistance indices and cardiovascular disease in middle-aged and elderly individuals: evidence from two prospectives nationwide cohort surveys - Li, Yan; Li, Huijuan; Chen, Xiaoyu; Liang, Xueyan (Frontiers in Endocrinology, 2024)
Background The estimated glucose disposal rate (eGDR), triglyceride glucose (TyG), triglyceride to high-density lipoprotein cholesterol ratio (TG/HDL-C), and metabolic score for insulin resistance (METS-IR) are dependent indicators of insulin resistance (IR). We aimed to evaluate the association between these indicators and the current or feature incidence of cardiovascular disease (CVD) in middle-aged and elderly individuals. This study tests the hypothesis that IR indices positively or negatively correlate with CVD, and that the potential predictive performance of the IR indices was not the same. Methods Middle-aged and elderly individuals from the National Health and Nutrition Examination Survey (NHANES) and the China Health and Retirement Longitudinal Study (CHARLS) with complete data on eGDR, TyG, TG/HDL-C, and METS-IR at baseline were obtained. The association between the four indices and CVD was evaluated using multivariate logistic regression analysis. In addition, an adjusted restricted cubic spline (RCS) was applied. Finally, the potential predictive performance of the IR indices was assessed using receiver operating characteristic (ROC) curves. Results We included 7,220 participants (mean age: 61.9 ± 10.7 years; 54.0% male) from the NHANES cohort and 6,426 participants (mean age: 57.9 ± 8.4 years; 45.2% male) from the CHARLS cohort in the study. Multivariate logistic regression analysis indicated that a decreasing eGDR significantly increased the incidence of CVD both presently and in the future. Similarly, a higher TyG level and METS-IR were significantly associated with a higher incidence of CVD at both timeframes. However, the TG/HDL-C ratio was not significantly associated with CVD, heart disease, or stroke. No significant interactions were observed between the continuous or quartile variables of eGDR, TyG, TG/HDL-C, or METS-IR, and the incidence of various endpoints across most subgroups. The ROC curve indicated the superior predictive performance of the IR indices. Furthermore, the eGDR was superior to other IR indices for the prediction of CVD both at present and in the future in middle-aged and elderly individuals. Conclusion As continuous variables, eGDR, TyG, and METS-IR were significantly associated with the incidence of CVD, both currently and in the future, among middle-aged and elderly individuals. Notably, incorporating eGDR, TyG, or METS-IR and the basic